2013
DOI: 10.1038/ejcn.2013.118
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a meal on measures of impedance and percent body fat estimated using contact-electrode bioelectrical impedance technology

Abstract: Twenty minutes after eating, %BF increased due to elevations in impedance and body mass. As such, when precision is critical, we recommend adhering to the pretest fasting guidelines to avoid meal-induced alterations in %BF estimates. In addition, use of a consistent testing schedule may minimize normal %BF variation over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 14 publications
1
14
0
1
Order By: Relevance
“…Later, when using different methods involving contact electrode bioimpedance, Dixon et al . () reported a small increase in body fat (0.9–1.5%) after a meal.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Later, when using different methods involving contact electrode bioimpedance, Dixon et al . () reported a small increase in body fat (0.9–1.5%) after a meal.…”
Section: Discussionmentioning
confidence: 98%
“…In a more recent study (Dixon et al, 2009), the same group, using segmental bioelectrical impedance measurements, found that %BF increased by 1-1.2% after drinking water or a carbohydrate electrolyte containing drink, probably as a result of the increase in body weight, with no difference between the two types of drink. Later, when using different methods involving contact electrode bioimpedance, Dixon et al (2013) reported a small increase in body fat (0.9-1.5%) after a meal.…”
Section: Discussionmentioning
confidence: 99%
“…Three of these studies reported increases in FM% after nutritional intake [ 14 , 24 , 25 ], which was different from our results. In contrast to our study, those previous studies used other BIA methods (segmental, multi frequency [ 14 ] and leg to leg [ 14 , 24 ]), had subjects remain in supine position for 12 h [ 25 ], included different time points for non-fasting measurements (20,40, and 60 min after eating) [ 14 ], or provided a higher energy intake (919 kcal [ 14 ], and 869 kcal [ 24 ]). Only two studies used wholebody SF BIA outcomes; one among healthy subjects [ 13 ] and one among elderly [ 26 ], and their results studies were similar to our study.…”
Section: Discussionmentioning
confidence: 88%
“…Participants were advised not to eat and drink for at least 4 hours prior to the appointment instead of an overnight fast. However, according to studies in people with normal weight and healthy people, the impact of drinks and food on BIA‐derived body composition values is present but absolutely small and might even be smaller in people with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of body composition is often recommended to be used in different clinical settings , and BIA is a simple and feasible method for this purpose. Still, many clinicians do not rely on BIA because it is not yet accepted as meeting clinical standards.…”
Section: Discussionmentioning
confidence: 99%